TIGA FASE PERKEMBANGAN BAHASA INDONESIA (1928—2009): KAJIAN LINGUISTIK HISTORIS - Sudaryanto Sudaryanto (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Indonesian language experienced three phases of development since its birth on October 28, 1928 until the issuance of Law Number 24 Year 2009 on Flag, Language, and Symbol of the Country, and National Anthem. The three phases it covers (1) Indonesian as a language of unity, (2) Indonesian as a country language, and (3) Indonesian as a international language. Research method used is content analysis. Data sources used are books, documentation, and photographs that record Indonesian events over 81 year. The results of this study indicate that (1) the phase Indonesian as a language of unity is marked van Ophuijsen of Spelling and the Indonesian Congress I, (2) the phase Indonesian as a country language is marked Article 36 of the 1945 Constitution, Indonesian Congress II, National Political Language Praseminar (1974), National Political Language Seminar (1975), Political Language Seminar (1999), Suwandi Spelling (1947), and Improved Spelling (1972), and (3) the phase of Indonesian as a international language marked Indonesian Congress International IX, Law Number 24 Year 2009, and the Center of Strategy Development and Linguistic Diplomacy, The Development Agency and Language Coachin. Keywords: Indonesian, language of unity, country language, international language Abstrak Bahasa Indonesia mengalami tiga fase perkembangan sejak kelahirannya pada 28 Oktober 1928 hingga terbitnya Undang-Undang Nomor 24 Tahun 2009 tentang Bendera, Bahasa, dan Lambang Negara, serta Lagu Kebangsaan. Tiga fase itu mencakup (1) bahasa Indonesia sebagai bahasa persatuan, (2) bahasa Indonesia sebagai bahasa resmi negara, dan (3) bahasa Indonesia sebagai bahasa internasional. Metode penelitian yang digunakan ialah analisis konten. Sumber data yang digunakan ialah buku, dokumentasi, dan foto yang merekam peristiwa bahasa Indonesia selama kurun waktu 81 tahun. Hasil penelitian ini menunjukkan bahwa (1) fase bahasa Indonesia sebagai bahasa persatuan ditandai Ejaan van Ophuijsen dan Kongres Bahasa Indonesia I, (2) fase bahasa Indonesia sebagai bahasa resmi negara ditandai Pasal 36 UUD 1945, Kongres Bahasa Indonesia II, Praseminar Politik Bahasa Nasional (1974), Seminar Politik Bahasa Nasional (1975), Seminar Politik Bahasa (1999), Ejaan Suwandi (1947), dan Ejaan yang Disempurnakan (1972), dan (3) fase bahasa Indonesia sebagai bahasa internasional ditandai Kongres Internasional IX Bahasa Indonesia, UU Nomor 24 Tahun 2009, dan Pusat Pengembangan Strategi dan Diplomasi Kebahasaan Badan Pengembangan dan Pembinaan Bahasa. Kata kunci: bahasa Indonesia, bahasa persatuan, bahasa negara, bahasa internasional